The impact of secondary information on consumers’ willingness to pay for differentiated fresh lamb meat products in South Africa - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.